2012
DOI: 10.1021/ac3031114
|View full text |Cite
|
Sign up to set email alerts
|

Nanopeptamers for the Development of Small-Analyte Lateral Flow Tests with a Positive Readout

Abstract: There is a great demand for rapid tests that can be used on-site for the detection of small analytes, such as pesticides, persistent organic pollutants, explosives, toxins, medicinal and abused drugs, hormones, etc. Dipsticks and lateral flow devices, which are simple and provide a visual readout, may be the answer, but the available technology for these compounds requires a competitive format that loses sensitivity and produces readings inversely proportional to the analyte concentration, which is counterintu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…The midpoint of the titration curve, corresponding to the concentration of analyte giving 50% of signal saturation (SC 50 ) was 2.2 ± 0.3, and the limit of detection (LOD = analyte concentration giving a 10% increase over the zero signal) was 0.48 ng/mL. These parameters are essentially the same that were obtained with the nanopeptamers prepared with streptavidin-HRP functionalized with biotinylated peptides, 11 showing that the variations in the attachment point to the streptavidin oligomer (Figure 1 ) do not have a major effect in the overall avidity of the complex for the IC. When these values are compared to the performance of the competitive assay set up with the same antibody, SC 50 = 28 ± 1.1 ng/mL and LOD = 4.0 ng/mL, it becomes evident that the recombinant nanopeptamer assay performs with increased sensitivity, representing an improvement of about 13 and 8 fold, respectively.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The midpoint of the titration curve, corresponding to the concentration of analyte giving 50% of signal saturation (SC 50 ) was 2.2 ± 0.3, and the limit of detection (LOD = analyte concentration giving a 10% increase over the zero signal) was 0.48 ng/mL. These parameters are essentially the same that were obtained with the nanopeptamers prepared with streptavidin-HRP functionalized with biotinylated peptides, 11 showing that the variations in the attachment point to the streptavidin oligomer (Figure 1 ) do not have a major effect in the overall avidity of the complex for the IC. When these values are compared to the performance of the competitive assay set up with the same antibody, SC 50 = 28 ± 1.1 ng/mL and LOD = 4.0 ng/mL, it becomes evident that the recombinant nanopeptamer assay performs with increased sensitivity, representing an improvement of about 13 and 8 fold, respectively.…”
Section: Resultssupporting
confidence: 61%
“…To work-around these limitations, we recently demonstrated that the phage particles can be substituted by commercial conjugates of streptavidin or avidin loaded with synthetic anti-IC peptides that contain a biotinylated lysine in their N-terminus. 11 These complexes, that we termed nanopeptamers, could be used to develop two-site noncompetitive assays for small molecules, which performed with similar sensitivity and specificity than their parent anti-IC phage particles.…”
mentioning
confidence: 99%
“…9 This indicates that the spatial distribution of the peptides in the VTX nanopeptamer allows attainment of a similar avidity interaction with the immobilized IC than that achieved with the streptavidin or the phage display. Moreover, using the midpoint of the assay titration curve for comparison, the SC 50 of the pA-VTX molinate assay was ∼13-fold more sensitive than the IC 50 (analyte concentration causing 50% inhibition) of the competitive ELISA set-up with the same antibody (IC50 69 ± 0.5 ng/mL).…”
Section: Results and Discusionmentioning
confidence: 91%
“…Therefore, various immunoassays, including enzyme-linked immunosorbent assay (Wei et al, 2018 ; Liu et al, 2019 ), lateral-flow immunochromatography (LFIC) (Li et al, 2010 ), and other novel immune sensors (Fernández et al, 2010 ; Zeng et al, 2019 ) have been developed for the detection of various antibiotic residues in milk. Of these assays, LFIC is the simplest method and the most rapid to carry out (Vanrell et al, 2013 ). Most LFIC experiments employ colloidal gold (CG) as labels to achieve qualitative or quantitative analysis of analytes (CháferPericás et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%